Sacha Inchi (Plukenetia volubilis L.) powder: acute toxicity, 90 days oral toxicity study and micronucleus assay in rodents - Idania Rodeiro; Diadelis Remirez; Diana Flores (GarVal Editorial Ltda., 2018)
Context: Sacha Inchi has been consumed for years by indigenous peoples. Meanwhile, its toxicological potential has not been sufficiently studied. Aims: To assess the acute, sub-chronic toxicity and genotoxicity evaluation of Sacha Inchi powder obtained from Plukenetia volubilis L. Methods: A dose of 2000 mg/kg was orally administered to rats and mice and toxicity symptoms for 14 days were observed. In repeated dose study, the product was orally administered to Sprague Dawley rats of both sexes. Animals received 50, 250 and 500 mg/kg/day of the product for 90 days. At the end, animals were sacrificed and samples were done for hematological and biochemical analysis, organ weighs and histopathological examination. Genotoxicity potential of Sacha Inchi powder was evaluated through micronucleus test in mice. Negative controls received the vehicle (carboxymethyl cellulose, 0.5%) used. Results: No morbidity or mortality at 2000 mg/kg of the product were found. Sacha Inchi powder oral administration during 90 days to rats did not lead to death, body weight gain, food consumption, or adverse events. No significant changes on hematological or biochemical parameters, organ weights or histopathological findings were observed. Induction of micronucleus formation attributable to the product was not found in mice. Conclusions: No toxicity effects after oral acute exposure of Sacha Inchi power to rats and mice were observed. Neither toxicity attributable to oral doses of the product up to 500 mg/kg during 90 days to rats were found. Results suggested Sacha Inchi powder does not have genotoxicity potential under our experimental conditions.